Application time and persistence of transcranial direct current stimulation (tDCS) against neuronal death resulting from transient cerebral ischemia - Jong-Hun Lee; Bo Hyun Jung; Ki-Yeon Yoo (Laboratory Animal Research, 2022)
Abstract Background Transcranial direct current stimulation (tDCS) has been studied as a tool to stimulate the functional recovery of neurons after stroke. Although this device has recently begun to be utilized for providing neuroprotection in stroke, research on its application conditions is lacking. This study aimed to examine the effects of various tDCS application conditions on cerebral ischemia. Ischemia was induced for 5 min in a gerbil model. The application of tDCS comprised a 20 min stimulation—20 min rest—20 min stimulation protocol, which was implemented simultaneously with the induction of cerebral ischemia. Application time of the tDCS effect on ischemia was confirmed by sampling brain tissues after stimulation using 0.2 mA tDCS at 0, 5, 10 and 60 min after ischemia. Results Persistence of the tDCS effect on ischemia was confirmed by sampling brain tissues 5, 7, and 10 days post stimulation, with 0.2 mA tDCS after ischemia. Furthermore, the tissues were stained with cresyl violet and Fluoro-Jade C so as to determine the reduction in neuronal death under all application conditions. Conclusions The application of tDCS can be used as a useful intervention for acute phase stroke due to its sustained neuroprotective effect.